2017
DOI: 10.18203/2319-2003.ijbcp20171116
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Phyllanthus fraternus against cyclophosphamide-induced nephrotoxicity in rats

Abstract: Background: Cyclophosphamide is commonly used against malignancies, such as leukemia and solid organ cancers. It can induce nephrotoxicity in cancer patients thereby complicating the initiation of chemotherapy. The study is to evaluate the effect of Phylllanthus fraternus against cyclophosphamide induced nephrotoxicity in albino rats.Methods: In this study, a total of 20 albino rats were divided into four groups of five each. Group I (normal control) received i.p. injection of normal saline. While, group II, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The increased levels of urea and creatinine are considered as the marker of impaired kidney functions [27,28]. Thus, in our study, an increase of plasma urea and creatinine reflected the diagnosis of renal damage.…”
Section: Discussionmentioning
confidence: 50%
“…The increased levels of urea and creatinine are considered as the marker of impaired kidney functions [27,28]. Thus, in our study, an increase of plasma urea and creatinine reflected the diagnosis of renal damage.…”
Section: Discussionmentioning
confidence: 50%
“…The finding of this study indicates that alloxan-induced diabetic in the rat at a dose (150 mg per kg) resulted in a significant increase serum liver enzymes (ALT and AST) and kidney functions (serum urea, uric acid and creatinine levels) compared with normal rats. Moirangthem et al, (36) reported that the increased levels of urea and creatinine are considered as the marker of impaired kidney functions. In this study, diabetic rats fed with 7.5% of A. halimus leaves powder treatment significantly (p<0.01) decreased the raised serum urea and creatinine, this means maintained healthy kidney function, and significantly restored the liver enzymatic activity compared with positive control.…”
Section: Discussionmentioning
confidence: 99%